2016
DOI: 10.5812/ircmj.24690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Oil Supplementation on Gestational Diabetes Mellitus (GDM): A Systematic Review

Abstract: ContextOne of the most common complications of pregnancy is gestational diabetes mellitus (GDM), which is increasing worldwide. Experimental and epidemiological studies have shown that higher intake of n-3 long-chain polyunsaturated fatty acids may decrease the risk of various diseases such as diabetes. The objective of this study was to assess the effect of fish oil supplementation on the prevention and treatment of GDM.Evidence AcquisitionThis systematic review was performed by searching several databases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…A few micronutrients were supplemented to GDM women in previous studies but the intervention outcomes for the mother and child dyad showed mixed results. 32–34 Neither vitamin C nor vitamin D intakes modified any growth outcomes or AL in our study, though in some pilot interventions they showed promising results. 34 However, since the sample size of this study is relatively small, it may not have enough power to detect all potential nutrient and health outcome associations.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A few micronutrients were supplemented to GDM women in previous studies but the intervention outcomes for the mother and child dyad showed mixed results. 32–34 Neither vitamin C nor vitamin D intakes modified any growth outcomes or AL in our study, though in some pilot interventions they showed promising results. 34 However, since the sample size of this study is relatively small, it may not have enough power to detect all potential nutrient and health outcome associations.…”
Section: Discussioncontrasting
confidence: 62%
“… 27–31 A few studies investigated the effects of nutrients such as antioxidants, docosahexaenoic acid (DHA), and vitamin D on improving GDM outcomes, targeting their roles in inflammation suppression and oxidative stress reduction, yet the results are preliminary and inconsistent. 32–34 Dietary habits such as higher fruit and lower vegetable consumption or higher fat preference have been associated with higher AL in non-pregnant populations with type 2 diabetes or metabolic syndrome. 6 35 AL is also suggested as a mediator between nutrient-based Dietary Approaches to Stop Hypertension diet score and all cause mortality in the 2001–2010 National Health and Nutrition Examination Surveys.…”
Section: Introductionmentioning
confidence: 99%
“…EPA and DHA have been widely reported to have protective functions for GDM patients [44][45][46]. However, EPA and Note: n = 268 in the interventional group and n = 270 in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these results, a systematic review from 2016 did not find any effect of fish oil supplements on FPG, Homeostatic model assessment-Beta cell function, or lipid profiles. It was concluded that there is not enough evidence to support the routine use of fish oil supplements during pregnancy in the treatment of diabetes [ 78 ].…”
Section: Fatmentioning
confidence: 99%